Role of eicosanoids, nitric oxide, and afferent neurons in antacid induced protection in the rat stomach. Issue 3 (March 1993) - Lambrecht, N; Trautmann, M; Korolkiewicz, R; Liszkay, M; Peskar, B M
Abstract : The mechanism underlying the mucosal protective effect of antacids is still unclear. This study shows that in rats the aluminum containing antacid, hydrotalcit, induces dose dependent protection against gastric mucosal damage caused by ethanol or indomethacin which is considerably enhanced by acidification. Hydrotalcit did not increase gastric mucosal formation or the intraluminal release of prostaglandins, and did not prevent the increase in mucosal leukotriene C4 formation in response to ethanol. Pretreatment with indomethacin did not attenuate the protective effect of unmodified or acidified hydrotalcit. Furthermore, hydrotalcit significantly reduced the gastric damage caused by indomethacin even when it was administered up to 2 hours after the ulcerogen. In indomethacin treated rats, simultaneous administration of hydrotalcit did not affect the concentrations of indomethacin in serum or inflammatory exudates nor did it attenuate the inhibition of prostaglandin release into the exudates. In hydrotalcit treated rats there was no attenuation of the increase in sulphidopeptide leukotriene release or decrease in leukocyte influx into inflammatory exudates elicited by indomethacin administration. Functional ablation of afferent neurons and inhibition of endogenous nitric oxide partially antagonised the protective effect of unmodified, but not of acidified, hydrotalcit. It is concluded that (i) the protective effect of unmodified and acidified hydrotalcit is independent of the eicosanoid system; (ii) protection against indomethacin induced gastric lesions does not require treatment before dosing of the ulcerogen and does not interfere with absorption and anti-inflammatory actions of indomethacin; (iii) endogenous nitric oxide and afferent neurons contribute partly to the effect of unmodified, but not of acidified, hydrotalcit suggesting that different mechanisms mediate their mucosal protective activity.